Local tissue damage induced by Bothrops snake venoms - A review - Gutiérrez, José María (1989)
This review focuses on the local effects induced by Bothrops venoms. These envenomation are characterized by myonecrosis, hemorrhage and edema which develop rapidly after venom inoculation. Myonecrosis is caused (a) directly, due to the direct action of myotoxins on the plasma membrane of muscle cells, and (b) indirectly, through the development of ischemia resultant from drastic alterations induced by these venoms on both microvasculature and intramuscular arteries. Regarding components that can be classified as “myotoxins with phospholipase A2 structure”, although some of them lack this enzymatic effect. These myotoxins have been purified from the venoms of Bothrops asper, B. jararacussu, and B. nummifer. Local hemorrhage in bothropic envenomation results from the action of acidic metalloproteins of relatively high molecular weight which act directly on the capillary vessels inducing extravasation. Five hemorrhagic toxins have been isolated an characterized from venoms of B. jararaca and B. neuweidi. Local edema is also a typical feature after injection of Bothrops venoms. This effect is probably due to: (a) Direct action of venom components on the microvasculature, increasing the permeability of capillaries and venules, and (b) the effect of endogenous mediators released by venom components. Among these mediators are histamine, prostaglandins, kinins, C3a and C5a. Besides edema, inoculation of Bothrops venoms elicits a prominent cellular inflammatory infiltrate. The need of a comprehensive approach in the study of snake venom-induced local tissue damage is stressed.